Factors associated with treatment satisfaction in patients with hidradenitis suppurativa: results from the Global VOICE project. (3rd September 2022) - Midgette, Bria; Strunk, Andrew; Akilov, Oleg; Alavi, Afsaneh; Ardon, Christine; Bechara, Falk G.; Cohen, Arnon D.; Cohen, Steven; Daveluy, Steven; del Marmol, Véronique; Delage, Maïa; Esmann, Solveig; et al.
Abstract: Background: Nearly half of patients with hidradenitis suppurativa (HS) report dissatisfaction with their treatment. However, factors related to treatment satisfaction have not been explored. Objectives: To measure associations between treatment satisfaction and clinical and treatment‐related characteristics among patients with HS. Methods: Treatment satisfaction was evaluated utilizing data from a cross‐sectional global survey of patients with HS recruited from 27 institutions, mainly HS referral centres, in 14 different countries from October 2017 to July 2018. The primary outcome was patients' self‐reported overall satisfaction with their current treatments for HS, rated on a five‐point scale from 'very dissatisfied' to 'very satisfied'. Results: The final analysis cohort comprised 1418 patients with HS, most of whom were European (55%, 780 of 1418) or North American (38%, 542 of 1418), and female (85%, 1210 of 1418). Overall, 45% (640 of 1418) of participants were either dissatisfied or very dissatisfied with their current medical treatment. In adjusted analysis, patients primarily treated by a dermatologist for HS had 1·99 [95% confidence interval (CI) 1·62–2·44, P < 0·001] times the odds of being satisfied with current treatment than participants not primarily treated by a dermatologist. Treatment with biologics was associated with higher satisfaction [odds ratio (OR) 2·36, 95% CI 1·74–3·19, P < 0·001] relative to treatment with nonbiologic systemic medications. Factors associated with lower treatment satisfaction included smoking (OR 0·78, 95% CI 0·62–0·99; active vs. never), depression (OR 0·69, 95% CI 0·54–0·87), increasing number of comorbidities (OR 0·88 per comorbidity, 95% CI 0·81–0·96) and increasing flare frequency. Conclusions: There are several factors that appear to positively influence satisfaction with treatment among patients with HS, including treatment by a dermatologist and treatment with a biologic medication. Factors that appear to lower treatment satisfaction include active smoking, depression, accumulation of comorbid conditions and increasing flare frequency. Awareness of these factors may support partnered decision making with the goal of improving treatment outcomes. What is already known about this topic? Nearly half of patients with hidradenitis suppurativa report dissatisfaction with their treatments. What does this study add? Satisfaction with treatment is increased by receiving care from a dermatologist and treatment with biologics. Satisfaction with treatment is decreased by tobacco smoking, accumulation of comorbid conditions including depression, and higher flare frequency. What are the clinical implications of this work? Awareness of the identified factors associated with poor treatment satisfaction may support partnered decision making and improve treatment outcomes. Abstract : Plain language summary available online